Estructura de la población de una sociedad de frontera: la Florida española, 1600 - 1763. - Arnaud Rabinal, J.I.; Bernárdez Álvarez, A.; Martín Escudero, P.M.; Pozo Redondo, F. del (Revista Complutense de Historia de América, 1991)
Sin resumen